Diagnostic performance of cone-beam computed tomography on detection of mechanically-created artificial secondary caries - Charuakkra,A. (Korean Academy of Oral and Maxillofacial Radiology, 2015)
Purpose: The aim of this study was to compare the diagnostic accuracy of cone-beam computed tomography (CBCT) images and bitewing images in detection of secondary caries. Materials and Methods : One hundred and twenty proximal slots of Class II cavities were randomly prepared on human premolar and molar teeth, and restored with amalgam (n=60) and composite resin (n=60). Then, artificial secondary caries lesions were randomly created using round steel No. 4 bur. The teeth were radiographed with a conventional bitewing technique and two CBCT systems; Pax-500ECT and Promax 3D. All images were evaluated by five observers. The area under the receiver operating characteristic (ROC) curve (A z) was used to evaluate the diagnostic accuracy. Significant difference was tested using the Friedman test (p value<0.05). Results : The mean A z values for bitewing, Pax-500ECT, and Promax 3D imaging systems were 0.882, 0.995, and 0.978, respectively. Significant differences were found between the two CBCT systems and film (p=0.007). for CBCT systems, the axial plane showed the greatest A z value. Conclusion : Based on the design of this study, CBCT images were better than bitewing radiographs in detection of secondary caries. © 2011 by Korean Academy of Oral and Maxillofacial Radiology.